Choroby i zaburzenia gruczołów piersiowych u dzieci - Malczyk, Żaneta; Kleszyk, Magdalena; Jarzumbek, Anna; Górowska-Kowolik, Katarzyna; Oświęcimska, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Disorders of the breast in children and adolescents, especially breast enlargement, concern both parents and pediatricians. Serious breast diseases requiring immediate diagnostic and therapeutic intervention are relatively rare in girls and boys. Each case with alarming symptoms, such as a tumor or premature breast enlargement, needs exclusion of organic changes. The aim of this study is to review the most common breast pathologies in children and adolescents. This article can help pediatricians and general practitioners carry out proper diagnostics and make the decision whether to refer the patient to the appropriate specialist: gynecologist, surgeon, endocrinologist or oncologist.